Pengaruh Eco Innovation dan Environmental Friendliness Terhadap Green Attitude, Green Purchase Intention dan Moderasi Willingness to Pay pada Fore Coffee - Amanda, Nur Anisa; Sadat, Andi Muhammad; Lutfia, Annisa (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of eco innovation and environmental friendliness on green attitude and green purchase intention, as well as to examine the moderating role of willingness to pay in the relationship between green attitude and green purchase intention at Fore Coffee. This research is motivated by the growing public awareness of environmental sustainability and the trend of consuming eco-friendly products, particularly in the coffee shop industry. A qualitative approach was employed using the PLS-SEM method with SmartPLS 4, involving 380 respondents from the Jabodetabek area who are active consumers of Fore Coffee. The results show that eco innovation and environmental friendliness have a positive and significant influence on green attitude and green purchase intention. Furthermore, green attitude positively affects green purchase intention. However, willingness to pay does not significantly moderate the relationship between green attitude and green purchase intention. These findings suggest that although consumers have a positive attitude toward eco-friendly products, it does not necessarily translate into a willingness to pay more. Therefore, more effective education and communication strategies are needed to enhance the perceived value of sustainable consumption. This study offers theoretical contributions to green consumer behavior research and practical recommendations for Fore Coffee’s green marketing strategies.